Perlindungan Hukum Terhadap Pemegang Hak Atas Tanah Setelah Diterbitkan Peraturan Daerah Kota Pekanbaru Nomor 07 Tahun 2020 Tentang Rencana Tata Ruang Wilayah Kota Pekanbaru Di Kota Pekanbaru - Rahmadani, Sutri; Firdaus, Firdaus; Firmanda, Hengki (Jurnal Ilmiah Wahana Pendidikan, 2025)
The issuance of Pekanbaru City Regional Regulation Number 07 of 2020 concerning Pekanbaru City Regional Spatial Planning, there was a significant impact on land rights holders. This regulation presents restrictions for land rights owners regarding the registration process, especially in efforts to upgrade SKGR to SHM because the land status has been changed to Green Open Space (RTH). This research focuses its attention on the land registration process, proving rights, and the implications of establishing RTH on land ownership. Therefore, an in-depth understanding of the mechanism for proving rights, relevance to applicable legislation, and legal protection measures taken by the Pekanbaru City regional government in the context of the status of land included in RTH are the main aspects emphasized in this research. This type of research is empirical (sociological), which uses empirical facts taken from data from the Pekanbaru City BPN and the Riau Province Regional Development Planning, Research and Development Agency as well as interviews with land rights holders and respondents related to this research. The research results show that in terms of legal protection for land rights holders whose status has changed to green open space areas, the Government, especially the Pekanbaru City BPN, provides legal rights to land in the form of use rights with a term limit of 25 years. To overcome the implications of including land in Green Open Space (RTH) in the RTRW, the Pekanbaru City Regional Government is trying to provide fair compensation for affected land owners. These steps not only ensure clarity in RTH designation but also provide appropriate incentives to affected land owners. The recommended approach involves a negotiation process and mutual agreement to determine a fair compensation value based on the area of land used for green open space.